Brain Morphological Modifications in Congenital and Acquired Auditory Deprivation: A Systematic Review and Coordinate-Based Meta-Analysis - Grégoire, Anaïs; Deggouj, Naïma; Dricot, Laurence; Decat, Monique; Kupers, Ron (Frontiers in Neuroscience, 2022)
The neuro-anatomical substrates of neuroplasticity following deafness are not well understood. Furthering our knowledge of neuroplastic changes due to deafness is of great importance since hearing loss is a growing problem due to an aging population. Moreover, knowing these brain changes could help to understand some disappointing results with cochlear implant therapy, and may therefore ultimately improve hearing rehabilitation. We conducted a systematic review and an anatomical likelihood estimation (ALE) meta-analysis of the morphological brain changes in patients suffering from severe to profound hearing loss, either congenital or acquired before or after language onset. A total of 25 papers were included in our review, encompassing more than 400 deaf subjects, most of them presenting prelingual deafness. The most consistent finding was a bilateral volumetric decrease in grey matter around the auditory cortex. This result was confirmed by the ALE meta-analysis which showed three clusters in this region. Another consistent finding was a grey matter decrease in the right cerebellum. In deaf children, there was an additional significant volumetric decrease of both the grey and white matter of the visual cortex. We discuss a number of factors that may modulate the effects of deafness on brain neuroplastic changes. One of the most important and best studied modulating factor is the use of sign language and its age of acquisition, which may induce changes within the hand motor region and the visual cortex. Other possible modulating factors which have been insufficiently studied are the etiology of the hearing impairment, speech-reading ability, hearing aid use, and frequently associated vestibular dysfunction or neurocognitive impairments. Our meta-analysis also revealed a relative lack of papers on neuroplastic changes in postlingual deafness, although this represents the largest cohort of the deaf population. Further studies are needed to better understand these issues, and finally try to improve deafness rehabilitation. We compare the results of the human literature with those obtained in animal models of deafness. Finally, we compare hearing loss with vision loss which is more consistently associated with grey matter and white matter decreases along the whole extent of the retinofugal visual pathways.